Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
`        If y=sin^-1(sina.sinx/1-cosa.sinx)Then y'(0) isA)1B)2sinaC)tanaD)sina`
one year ago

Arun
23366 Points
```							 Dear student when you differentiate this, you get an expression. now put x = 0 in this expression, you will get sin a hence y’(0) = sin a
```
one year ago
1807 Points
```							write siny= sinasinx/(1 – cosasinx)now differentiating wrt xcosy*y’(x)= sina[cosx(1 – cosasinx) + sinxcosxcosa]/(1 – cosasinx)^2when x=0, y=0so 1*y’(0)= sina/(1 – 0)= sina
```
one year ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Differential Calculus

View all Questions »

### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution

### Course Features

• 51 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions

Post Question